Identification and Expression of Conserved and Novel RNA Variants of Medaka pax6b Gene. Issue 5 (26th May 2017) - Chen, Tiansheng; Cavari, Benzion; Schartl, Manfred; Hong, Yunhan
GRAPHICAL ABSTRACT: Medaka pax6b gene contains the conserved enhancers (A‐H) and multiple usage of promoters (P0‐P7a). Alternative splicing of different exons and promoters produced 43 RNA variants predicting six protein isoforms. Canonic expression pattern was validated in brain, eye and pancreas, and several major RNA variants had apparently differential expression in these organs. ABSTRACT: Gene duplication is a major driving force of evolution. How gene duplicates have evolved remains a mystery. A highly conserved gene such as Pax6 is an ideal model to study functional conservation and divergence via comparisons among diverse organisms. One pax6 gene has been characterized in the Japanese medaka ( Oryzias latipes ), which is annotated as pax6b on chromosome 3. Here, we report that Medaka pax6b is homolog to Pax6 of mammals in sequence, chromosomal synteny, and genomic organization. Cloning and sequencing led to the identification of up to 43 pax6b RNA variants predicting six protein isoforms, 22 of which are similar to those reported in other organisms and 21 represent novel RNA variants. By RT‐PCR, the pax6b transcripts were found to be most abundant in the adult eye and easily detectable in the adult brain and pancreas but not detectable in developing embryos until gastrulation. Interestingly, apparently differential expression in adult organs was observed for several major variants. In situ hybridization revealed that pax6b exhibited highly conserved RNA expression in pancreas, brain, and eye of adult animals and developing embryos. Therefore, by sequence, chromosomal synteny, gene structure, conserved alternative transcription and splicing, and most importantly, conserved expression patterns in adulthood and embryogenesis, medaka pax6b represents a ortholog of Pax6 gene in mammals and is capable of generating differentially expressed RNA variants.